Green technology : an A-to-Z guide - Mulvaney, Dustin (Sage reference series on green society., 2011)
"Green Technology: An A-to-Z Guide explores the essential role of technology and its most recent developments toward a sustainable environment. Twofold in its definition, green technology includes the changing of existing technology toward energy conservation as well as the creation of new, clean technology aimed at utilizing renewable resources. With a primary focus on waste management, the volume presents more than 150 articles in A-to-Z format featuring such disciplines as nanoscience, biochemistry, information technology, and environmental engineering. Scholars and experts in their fields present a full range of topics from applications of green technology to The Green Grid global consortium to membrane technology and water purification systems to waste-to-energy technology. This work culminates in an outstanding reference available in both print and electronic formats for academic, university, and public libraries. Vivid photographs, searchable hyperlinks, an extensive resource guide, numerous cross references, and a clear, accessible writing style make the Green Society volumes ideal for classroom use as well as for research"--